2019
DOI: 10.3390/medicina55050173
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Maternal Diet on Human Milk Composition Among Lactating Women in Latvia

Abstract: Background and objectives: Many studies indicate that the maternal diet is an important factor affecting human milk composition. Human milk composition among lactating women in Latvia, as well as the maternal diet during lactation, has not been sufficiently studied. The aim of this research was to assess dietary habits and macronutrient intake among lactating women in Latvia and to examine the effect of diet on human milk composition. Materials and Methods: Research was conducted between November 2016 and Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
94
3
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(107 citation statements)
references
References 47 publications
4
94
3
6
Order By: Relevance
“…The current finding could be explained by direct transfer of maternal dietary proteins from plasma to BM which adds to the protein synthesized in the mammary secretory cell. In contrary to studies of Bauer and Gerss [36], and Aumeistere et al [37], both revealed that concentration of HM protein is not affected by maternal diet.…”
Section: Discussioncontrasting
confidence: 64%
“…The current finding could be explained by direct transfer of maternal dietary proteins from plasma to BM which adds to the protein synthesized in the mammary secretory cell. In contrary to studies of Bauer and Gerss [36], and Aumeistere et al [37], both revealed that concentration of HM protein is not affected by maternal diet.…”
Section: Discussioncontrasting
confidence: 64%
“…The intra-population variance of the HM samples can be determined by many factors, including maternal diet. The influence of maternal diet on the HM fatty acid composition has been very well documented [ 38 , 39 , 40 , 41 ]; however, the correlation between other lipids and maternal diet still requires investigation. High variance in lipid composition between mothers observed in this study can also suggest that HM lipid composition changes according to the actual needs of the infant.…”
Section: Discussionmentioning
confidence: 99%
“…In light of this, variations in human milk fatty acid composition between individuals and populations have been attributed to cultural differences (such as diet and other lifestyle factors) (6)(7)(8)(9)(10) (11) and human genetic differences (12,13) amongst others. Human milk fatty acid composition can therefore reflect both dietary sources and endogenous biological synthesis of fatty acids (14)(15)(16)(17) .…”
Section: Introductionmentioning
confidence: 99%